The inhibition of Fusarium wilt in Chili by Endophytic Fungi isolated from Green Betel (Piper betle L.) Leaf - Andang Syaifudin; Rina Sri Kasiamdari (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2022)
Green Betel (Piper betle L.) leaves are often used as medicine by local people because they contain antibacterial and antifungal substances. These substances can be produced by plant metabolites and are also the results of metabolites produced by endophytic fungi. Endophytic fungus is an organism that is associated with healthy host tissues without causing disease symptoms. Endophytic fungi from betel leaf are used as biocontrol agents against Fusarium oxysporum causes wilt disease that attacks Chili (Capsicum annuum L.), which is one of the main agricultural commodities in Indonesia. Fusarium wilt disease is a disease that significantly reduces crop yields based on crop yields. This research was conducted in a chili farm in Cangkringan, Sleman, Yogyakarta. This study aimed to test the antagonism of endophytic fungi with the dual culture technique. Three types of green betel leaf endophytic fungi were used for dual culture test against Fusarium oxysporum. The observation result showed the highest inhibition ability of 73.37% dual culture method. The inhibitory mechanisms of green betel leaf endophytic fungal isolates include parasitism, antibiosis, and competition. Endophytic fungi of green betel leaf are effective as biocontrol agents of wilt Fusarium chili disease. ©2022 JNSMR UIN Walisongo. All rights reserved.